A Comprehensive Review of Trayopasthambhas Role in Promoting Healthy Aging (AYUSHDHARA, 2024)
Trayopasthambha, the fundamental tool in Ayurveda, is essential for preserving a healthy lifespan. Tridanda (Satva, Aatma and Shareera) act as a main pillar according to Charaka and Tridosha (Vata, Pitta and Kapha) act as main pillars according to Acharya Sushruta and these two will be supported by the sub pillars called Trayopastambha. Hence the sub-pillars (Trayopastambha) have been given equal importance as the main pillars (Tridanda and Tristoona) and considered as one of the fundamental factors to stay healthy. Trayopastambha stands as a foundational tool inherent to every human being, essential for safeguarding their destined life. Intricately linked with the three pillars of existence, it sustains well-being and preserves life's vitality. Aging is natural and unavoidable, affected by lifestyle and genetics. Ahara (diet), Nidra (sleep), and Brahmacharya (balanced living) significantly influence aging. Proper use promotes healthy aging, while neglect accelerates aging, causing premature decay.